West African Economic and Monetary Union : Staff Report on Common Policies of Member Countries. (IMF Staff Country Reports; Country Report ;, 2015)
KEY ISSUES Context. The region continued to experience strong growth in 2014, led by the continued economic expansion in Cote d'Ivoire. The outlook is for further strong growth, subject to a range of downward risks, in particular political instability ahead of upcoming elections in several countries, and security issues in Mali and Niger. With an elevated fiscal deficit exerting pressure on the balance of payments and the regional financial market, delays in fiscal consolidation or structural reforms pose the main medium-term risks. Policy recommendations: -- Fiscal consolidation. Safeguarding external stability in the region will require governments to adhere to their budget deficit reduction plans while maintaining public investment efforts, which will require increasing tax revenue and controlling current expenditure. -- Monetary policy. Macroeconomic conditions do not warrant a tightening of monetary policy at this juncture. However, if fiscal deficits do not decline as envisaged, the BCEAO should consider increasing its policy rates. In the mean time, the BCEAO should very closely follow the evolution of the macro-prudential risks flowing from its sharp increase in commercial bank refinancing. -- Financial stability. The WAEMU authorities should enforce existing prudential rules and raise standards to international best practice. Ongoing reforms go in the right direction but need to be accelerated. -- Structural transformation and regional integration. Policies to promote structural transformation should focus on addressing weaknesses, such as the lack of education and training, finance, and supportive regulatory environments. Countries should refrain from using the possibility to deviate from the common external tariff of the Economic Community of West African States (ECOWAS) in force since January 1, 2015, in order to protect the gains from regional integration in WAEMU.